Nawrouz in Arabic Literary Resources "Historical Study - Salim, Lulav M. (Humanities Journal of University of Zakho, 2018)
The study (Nawroz in Arabic Literature) is one of the important and famous holidays when many nations. due to the foot and the importance of this feast has sung a lot of poets appropriate that. we talked about those features from the viewpoint of poets and writers in the Arab literature. And differed description poets and writers in the festival Nawroz description Each of them he describes his own way. There are those who focused on the natural side of where the atmosphere of nature and climate change. and there are those concerned with aesthetics to show picturesque features of nature and painted in all colors of the spectrum. And the others did not enjoy the joy of feast because of the grief and pain that they feel, they talked about their joy of Nawroz sad. And shows the ritual prevailing in the holiday Nawroz of pouring water and caught fire, etc, as well as the economic side that which is not separated from those feasts of the collection of the abscess and gifts obtained by princes and kings, and other descriptions expressed by poets and writers that occasion, and then mention of the main conclusions reached by study.